Genealogi Keilmuan Santri dan Dinamika Islam Nusantara dalam Tradisi Pendidikan Pesantren: Studi Kasus di Pondok Pesantren Nadhratul Ulum, Kalibeber Wonosobo - Agus Maulana Firdaus; M. Arja Habibi; Nadya Farkha Salsabila Mubarok3 (Al Jabiri: Jurnal Ilmiah Studi Islam, 2025)
This study aims to analyze the role of Pondok Pesantren Nadhratul Ulum in preserving and developing Islam Nusantara through the scholarly traditions of the santri, as well as how the pesantren adapts to social, political, and technological changes. Using a qualitative descriptive approach and case study, this research collects data through in-depth interviews with pesantren leaders, teachers, students, and alumni, as well as observations of the educational processes at the pesantren. The main findings of the study show that this pesantren successfully preserves the identity of Islam Nusantara through the teaching of kitab kuning (traditional Islamic texts) that link Islamic teachings with local Indonesian culture. In addition, Pondok Pesantren Nadhratul Ulum also demonstrates adaptation to the changing times by utilizing technology in learning, while still maintaining traditional teaching methods such as halaqah (study circles). The study also highlights that the integration of technology is done carefully to support the learning process without compromising the direct interaction between teachers and students, which is considered the core of pesantren education. These findings provide insights into how pesantren in Indonesia can adapt to globalization and modernity without losing the essence of the traditions that have existed. This research is expected to contribute to a deeper understanding of the role of pesantren in contemporary Islamic education, particularly in the context of Islam Nusantara.